Evaluating the Effectiveness of Gamification in Online Education: Strategies for Promoting Active Learning and Student Retention - Riza Hamid; Zaid Barzenji (Yayasan Azhar Amanaa Yogyakarta, 2024)
This qualitative study explores the impact of gamification on active learning and student retention in online education. It investigates the influence of game elements such as points, badges, leaderboards, and collaborative challenges on engagement and motivation among students, educators, and administrators across diverse educational settings. The study utilizes semi-structured interviews, focus groups, surveys, and observations to gather comprehensive insights into participant experiences. The findings highlight that gamification significantly enhances student engagement by offering clear objectives, immediate feedback, and a sense of accomplishment. Participants express heightened motivation and enjoyment in their learning activities, leading to increased participation levels and reduced dropout rates. Nonetheless, challenges such as balancing competitive elements and aligning gamified activities with educational goals are identified as areas for improvement. This research contributes to a deeper understanding of how gamification can effectively transform online learning environments. It offers practical recommendations for educators and institutions to optimize student engagement and retention through the strategic implementation of gamified strategies